2018
DOI: 10.1194/jlr.d081414
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of HETEs in human whole blood by chiral UHPLC-ECAPCI/HRMS

Abstract: The biosynthesis of eicosanoids occurs enzymatically via lipoxygenases, cyclooxygenases, and cytochrome P450, or through nonenzymatic free radical reactions. The enzymatic routes are highly enantiospecific. Chiral separation and high-sensitivity detection methods are required to differentiate and quantify enantioselective HETEs in complex biological fluids. We report here a targeted chiral lipidomics analysis of human blood using ultra-HPLC-electron capture (EC) atmospheric pressure chemical ionization/high-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 49 publications
(62 reference statements)
4
24
0
Order By: Relevance
“…In line with a recent study (7), our chiral analysis showed that monohydroxy metabolites are generally present as racemates in the human circulation, whereas enantioselective responses occur after stimulating their de novo biosynthesis. Ca 2+ -ionophore stimulation resulted in specific increases of the (S)-enantiomers of those HETEs, HEPEs, and HDHAs that were apparently produced by the stereospecific actions of 5-, 12-, and 15-LOX enzymes expressed in different blood cells (48)(49)(50).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with a recent study (7), our chiral analysis showed that monohydroxy metabolites are generally present as racemates in the human circulation, whereas enantioselective responses occur after stimulating their de novo biosynthesis. Ca 2+ -ionophore stimulation resulted in specific increases of the (S)-enantiomers of those HETEs, HEPEs, and HDHAs that were apparently produced by the stereospecific actions of 5-, 12-, and 15-LOX enzymes expressed in different blood cells (48)(49)(50).…”
Section: Discussionsupporting
confidence: 90%
“…This method can be coupled with normal-phase chiral-LC and requires prior derivatization of oxylipins, e.g., into their pentafluorobenzyl esters (6). Using this sensitive approach, a recent study showed stereospecific responses to in vitro stimulation of human blood samples regarding the formation of HETEs (7). An alternative strategy takes advantage of chiral stationary phases that are compatible with water-containing polar mobile phases.…”
mentioning
confidence: 99%
“…leukotrienes) and triols (e.g. lipoxins) correlated strongly with the autooxidative markers (S6 Table) supporting an autooxidative origin [57,58]. A recent study of effects of long-term storage on the plasma metabolome reports general stability for up to 7yrs, with significant changes observed with additional time up to 16yrs [59].…”
Section: Plos Onementioning
confidence: 63%
“…During inflammation, infiltrating leukocytes exert their actions in part by the release of oxidative species. Although isoprostanes are considered markers of free radical induced lipid peroxidation/oxidative reactions several of the PUFA-derived oxylipins can be formed by autoxidation, wherein equal amounts of the R and S-enantiomer is produced (Mazaleuskaya et al, 2018). However, both 5-LOX and 15-LOX enzymes stereo-selectively produce hydroxylated lipids with the S-configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Chiral chromatography can therefore be essential to elucidate the biosynthetic source of production of specific lipid species. For example, 9(S)-and 9(R)-HETE were shown to be equally produced following lipopolysaccharide and/or zymosan stimulated human whole blood while 12(S)-and 15(S)-HETE were the main products (Mazaleuskaya et al, 2018).…”
Section: Oxylipin Generation By Ros and Rnsmentioning
confidence: 98%